Autologous platelet-rich plasma: evidence for clinical use. Issue 6 (November 2015) - Cohn, Claudia S.; Lockhart, Evelyn
Abstract : Purpose of review: Autologous platelet-rich plasma (aPRP) is growing in popularity as a therapy to augment wound healing, speed the recovery from muscle and joint injuries, and enhance recovery after surgical repair. High-profile athletes treated with aPRP have increased the demand from the general population. Yet, evidence to support the use of aPRP in most clinical settings is weak, because of poorly controlled clinical trials. Recent findings: Preparations of aPRP vary by platelet count, leukocyte content, and degree of platelet activation. Nonetheless, these heterogeneous preparations are used in trials to assess the efficacy of aPRP treatment. Summary: Despite weak evidence, the use of aPRP continues to grow. High-quality randomized controlled trials are needed to validate or repudiate the potential efficacy of aPRP. Standards for aPRP preparation and quality should be created.